Advancing SDGs 1 through Sustainable Microfinance Institutions: The Roles of Competition, Double Bottom Line Performance, and Digitalization. - Djoko Karyono; Djoko Suhardjanto; Irwan Trinugroho; Izza Mafruhah (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Objective: The study examines the financial and social performance of microfinance institutions (MFIs) and assesses whether digitalization and its interaction with institution size are associated with operational self-sufficiency and outreach. Method: The analysis uses an unbalanced panel from the MIX Marker database. The descriptive output covers 1999-2019 and contains up to 20,120 institution-year observations. Fixed-effects panel regressions are reported for operational self-sufficiency (OSS) and the number of active borrowers (NAB), with profitability, loan volume, capital adequancy, funding structure, proverty outreach, total assets, and digitalization as explanatory variables. Result: Return on assets in positively associated with OSS, while loan volume is strongly associated with NAB. A higher depositto-loan ratio is linked to stronger OSS. The share of cliencts below the proverty line is positively associated with OSS but negatively associated with NAB. The direct digitalization coefficient and the digitalization-total-assests interaction are statistically insignificant in the reported models. Novelty: The study separates financial sustainability from social outreach and test whether digital maturity changes the size-performance relationship in an international MFI panel. The result show that digital adoption alone does not guarantee stronger double-bottom-line performance.